Private equity challenge: LBO of Auga group - Guimarães, Francisco Afonso da Costa (2022)
This Investment Committee Paper was performed by a group of students from the Master’s in Finance Program, being intended for academic purposes only. The core objective of this work project is to assess AUGA’s attractiveness as an LBO target. The group elaborated a value creation strategy and an operating model for the investment proposal, backed by a full-blown company and market evaluation, and by the company’s valuation. The group suggested an optimal capital structure for the transaction and possible exit strategies, deriving potential returns for the fund on the exit year. This parts focuses then particularly on the company in depth analysis, its drivers and dynamics.